How does the modern football goalkeeper train? - An exploration of expert goalkeeper coaches` skill training approaches - Otte, F. W.; Millar, S.-K.; Klatt, S. (Journal of Sports Sciences, 2020)
The football goalkeeper position arguably represents a unique role within the team sport. Despite its highly complex skill demands, research on football goalkeeping has only sporadically examined the position within isolated and limited parameters. In particular, there is limited literature on "modern" skill acquisition training methods and approaches within the field of goalkeeper training. In a cross-cultural study with fifteen expert goalkeeper coaches, researchers here examined the overarching research question of "how does the modern football goalkeeper train?". Semi-structured interviews explored expert coaches` views on critical skills for performance in goalkeeping and the training approaches used to develop these critical skills. Results indicate that four skill sets are considered essential by goalkeeper coaches, these are: decision-making skills, athleticism, mentality, and technical skills. In terms of developing these skills in goalkeeper-specific training, the majority of expert coaches apply a similar microstructure to training sessions. This structure involves a steady progression from simple to complex training tasks, where for large parts, isolated technical training appears to be prioritised over a holistic training approach that integrates technical skills and perceptual-cognitive components (e.g., decision making). Scientific and practical recommendations for researchers and practitioners in the field of football goalkeeper coaching are provided.